2020
DOI: 10.1002/jum.15397
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Weight Estimation Using Automated Fractional Limb Volume With 2‐Dimensional Size Parameters in Diabetic Pregnancies

Abstract: Objectives To examine the effect of adding automated fetal fractional limb volume (FLV) with conventional 2‐dimensional (2D) fetal weight estimation procedures in a cohort of diabetic pregnancies. Methods A pilot study of diabetic pregnancies measured standard fetal biometry within 7 days of delivery. Fractional arm volume (AVol) and fractional thigh volume (TVol) soft tissue parameters were measured with a commercially available automated software utility (5D Limb Vol; Samsung Medison Co, Ltd, Seoul, Korea). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Automated FLV has been proven to work with diabetic pregnancies 22 . Random errors for the AVol (6.2%) and TVol (6.9%) models were significantly more precise than the other prediction models: Hadlock et al (7.8%), INTERGROWTH‐21st (8.0%), and Schild et al (8.6%) 22 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Automated FLV has been proven to work with diabetic pregnancies 22 . Random errors for the AVol (6.2%) and TVol (6.9%) models were significantly more precise than the other prediction models: Hadlock et al (7.8%), INTERGROWTH‐21st (8.0%), and Schild et al (8.6%) 22 .…”
Section: Discussionmentioning
confidence: 98%
“…Automated FLV has been proven to work with diabetic pregnancies 22 . Random errors for the AVol (6.2%) and TVol (6.9%) models were significantly more precise than the other prediction models: Hadlock et al (7.8%), INTERGROWTH‐21st (8.0%), and Schild et al (8.6%) 22 . The greatest proportion of cases with BW ±10% was also classified by the AVol (91.1%) and TVol (91.1%) models, followed by the Hadlock (83.3%), INTERGROWTH‐21st (78.9%), and Schild (76.7%) predictions 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic thresholds that use a cut-off of 4500 grams to designate macrosomia in the newborn are also likely to underestimate the frequency of fetal overgrowth in this population or for other populations where delivery before term is undertaken [ 10 ]. The need to explore improved models of estimated fetal weight or novel markers of fetal body composition, particularly amongst women with pregestational type 2 diabetes, is necessary to better refine risk prediction of intrapartum complications in this high-risk group [ 32 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication that investigated the growth of fetal limb volumes in fetuses with maternal gestational diabetes, AVol but not TVol was larger in the GDM group, indicating the ability of AVol to detect alterations of fetal body composition associated with gestational diabetes [16]. Another recent study of automated FLV and weight prediction in diabetic pregnancies also suggested slightly lower random error for weight models using AVol (6.2%), when compared to conventional 2D fetal weight estimation procedures using the TVol parameter (6.9%) [17].…”
Section: Discussionmentioning
confidence: 99%